Effect of basic public health service project on neonatal health services and neonatal mortality in China: a longitudinal time-series study. Issue 7 (20th July 2020) - Zhao, Pengyu; Han, Xueyan; You, Lili; Zhao, Yu; Yang, Li; Liu, Yuanli
Abstract : Objective: To analyse the trend change and level change of neonatal health services and neonatal mortality before and after the introduction of the Basic Public Health Service (BPHS) project in 2009. Design and setting: A national longitudinal study on neonatal mortality from 1991 to 2017 and neonatal health services from 2000 to 2017 was conducted based on data extracted from the National Neonatal Mortality Surveillance System and National Health Statistic Yearbook. The segmented linear regression model was used to assess the level changes and trend changes of the outcome variables before and after the introduction of BPHS project. Pearson correlation analysis as conducted to measure association between neonatal mortality rates (NMRs) and maternal health management rates (MMRs), neonatal visit rates, respectively. Primary and secondary outcome measures: The outcome variables were national NMR, the gap of NMR between urban and rural areas, maternal health management rate and neonatal visit rate. Results: The annual trend change coefficient of national NMR and the gap of NMR between urban and rural areas were −0.57 (p<0.01) and −0.49 (p<0.01) after the introduction of BPHS project, while the annual trend coefficient of the MMR and the neonatal visit rate were 1.21 (p<0.01) and 0.85 (p<0.01), respectively. The negative correlations were found between NMR and MMR (r=−0.79, p<0.01) and neonatal visit rate (r=−0.76, p<0.01). Conclusion: The BPHS project was found to be associated with increased volume of neonatal health services and reduced NMR. The design and implementation of this project may provide references to other low-income and middle-income countries.